NAVIGATING TRANSITIONS IN GREEN ARCHITECTURE: A MULTI-LEVEL PERSPECTIVE ON PHOTOBIOREACTOR-INTEGRATED FAÇADES IN INDONESIA - Chely Novia Bramiana; Budi Setyawan; Muhammad Azzam Ismail; Alexis Gerardus Entrop; Sukawi Sukawi (MODUL, 2025)
In tropical countries like Indonesia, architectural design faces the pressing challenge of mitigating excessive heat, humidity, and solar exposure, yet many buildings continue to adopt imported, non-contextual design models. This study explores the implementation and transitional trajectory of a novel microalgae-based photobioreactor (PBR) window façade—an innovation that integrates biological systems into building envelopes for thermal shading, light modulation, and ecological performance. Using the Multi-Level Perspective (MLP) framework, this research examines the interplay between niche experimentation, regime-level constraints, and landscape drivers shaping the adoption of green building technologies in Indonesia. The PBR façade, developed through a university–industry collaboration and installed in Semarang, demonstrates how architectural innovation can evolve through iterative learning, cross-sector collaboration, and real-environment testing. However, its broader uptake is constrained by entrenched design norms, lack of regulatory standards, and limited institutional mechanisms for certification. Landscape pressures such as ESG imperatives and climate adaptation goals offer promising opportunities, but systemic change requires alignment across policy, professional practice, and cultural narratives. The study contributes a process-oriented roadmap for embedding biologically integrated façades into the sustainability transition of tropical urban architecture.